The Correlation of Teacher Performance and Learning Methods with Learning Outcomes of Students’ Learning Al-Qur'an Hadits - Markaban Markaban; Imam Syafe’i; Siti Raudlatul Jannah (CV. Creative Tugu Pena, 2021)
The learning process was always monotonous or less varied, this meant that the learning outcomes of students were still low so that the learning process was less attractive to students. One of the efforts to improve the learning outcomes of students' Al-Qur'an-Hadith Lessons. This study is to apply a varied learning model that can improve student learning outcomes in the lessons of Al-Qur'an Hadith. Techniques in data collection in this thesis research researchers use the method of observation, questionnaires, interviews and documentation. Analysis of the data in this study using the product moment statistical analysis techniques, from the calculation it can be seen the conclusion about the correlation of teacher performance and learning methods to the learning outcomes of the Al-Qur'an Hadith for Class X. IPA.1 Students MA. Darul A'mal Kota Metro Academic Year 2019/2020, with a high correlation, namely with a total value of 0.811. If this value is correlated with r count = 0.811 if consulted with the value of r table, then the coefficient is a high influence, because rcount = 0.811 with db = n-2 = 22 greater than r table 5% = 0.423, or rcount = 0.811 is greater than rtable 1% = 0.537. r table 5% 0.423 smaller than r count 0.811 greater than 1% 0.537 can be written as 0.423 <0.811> 0.537 Keywords: Teacher Performance, Learning Method, Learning Outcome